2000
DOI: 10.1128/jb.182.19.5425-5432.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Secretory Tyrosine Phosphatases of Mycobacterium tuberculosis

Abstract: Two genes with sequence homology to those encoding protein tyrosine phosphatases were cloned from genomic DNA of Mycobacterium tuberculosis H 37 Rv. The calculated molecular masses of these two putative tyrosine phosphatases, designated MPtpA and MPtpB, were 17.5 and 30 kDa, respectively. MPtpA and MPtpB were expressed as glutathione S-transferase fusion proteins in Escherichia coli. The affinity-purified proteins dephosphorylated the phosphotyrosine residue of myelin basic protein (MBP), but they failed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 40 publications
(39 reference statements)
3
131
0
Order By: Relevance
“…It was observed that sodium sulphate had no inhibitory effect on phosphatase activity of SynPTP, which confirmed that Zn 2þ behaves as a potent inhibitor for SynPTP. On the other hand, it was observed that sodium fluoride, a non-specific inhibitor (33,42) for phosphatases and okadaic acid, a potent inhibitor (25) of many PP2A, failed to inhibit the catalytic activity of SynPTP. These results suggested that the sensitivity of the catalytic function of The catalytic activity of rSynPTP or mutagenically altered SynPTP was determined using 500 ng of each recombinant protein and 4 mM Casein ( 32 P-Tyr)/RCML ( 32 P-Tyr) or 10 mM pNPP as exogenous substrates as described in the 'Materials and Methods' section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that sodium sulphate had no inhibitory effect on phosphatase activity of SynPTP, which confirmed that Zn 2þ behaves as a potent inhibitor for SynPTP. On the other hand, it was observed that sodium fluoride, a non-specific inhibitor (33,42) for phosphatases and okadaic acid, a potent inhibitor (25) of many PP2A, failed to inhibit the catalytic activity of SynPTP. These results suggested that the sensitivity of the catalytic function of The catalytic activity of rSynPTP or mutagenically altered SynPTP was determined using 500 ng of each recombinant protein and 4 mM Casein ( 32 P-Tyr)/RCML ( 32 P-Tyr) or 10 mM pNPP as exogenous substrates as described in the 'Materials and Methods' section.…”
Section: Resultsmentioning
confidence: 99%
“…Third, we examined the catalytic activity of SynPTP by analysing effect of various phosphatase inhibitors to determine whether SynPTP displayed similar pattern of sensitivity towards these inhibitors as other known LMW PTPs (11,12,33,35,42). Ammonium molybdate, sodium orthovanadate and Zn 2þ are known to be potent inhibitors of PTPs (12,33,35), and our results suggested that these inhibitors strongly inhibited the activity of SynPTP (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…3) of the substrate entry site and is superimposable with the side chains of Asn 50 in BPTP (Fig. 5A) 49 in BPTP, which provides the ring-ring interactions on one side of the substrate ring. This factor may also contribute to the relatively lower substrate affinity of Wzb (K m of 1 mM) (13) compared with BPTP (0.38 mM) and LTP1 (0.017 mM) (7) using p-nitrophenyl phosphate as the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests that this kind of ringring contact is essential for the function of LMW-PTPs in both prokaryotes and eukaryotes. On the other side of the substrate, the loop ␤ 2 -␣ 2 of eukaryotic LMW-PTPs contains another aromatic residue (Tyr 49 in HCPTPA, Trp 49 in BPTP, and Tyr 51 in LTP1) that provides contacts with the substrate and closes the claw around it (9, 10). However, the loop ␤ 2 -␣ 2 of Wzb does not contain an aromatic residue that is equivalent to Trp 49 in BPTP.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, secretory phosphatases belonging to distinct families; (1) Proteintyrosine phosphatases (MptpA, MptpB), (2) Lipid phosphatases (SapM), and recently identified, (3) Phosphoserine phosphatase SerB2, have been identified as key molecules in the virulence of Mtb. The secreted tyrosine-phosphatase MptpA has been shown to interfere with phagosome acidification by inhibiting the trafficking of vacuolarATPase to phagosome [10,11]. MptpB, another secreted tyrosine-phosphatase has been shown to subvert the host immunity [12].…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%